Field Effectiveness of Bacillus thuringiensis israelensis (Bti) against Aedes (Stegomyia) aegypti (Linnaeus) in Ornamental Ceramic Containers with Common Aquatic Plants - Dhang, C.C.; Lim, L.H.; Ahmad, N.W.; Benjamin, S.; Weng, L.K.; Rahim, D.A.A.; Safian, E.S.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2009)
This study was undertaken to determine the impact of larvaciding using a Bti (Bacillus thuringiensis israelensis) formulation (VectoBac WG) against Aedes aegypti larvae in earthen jars containing aquatic plants. Aquatic plants commonly used for landscaping, Pistia stratiotes (L.) (Liliopsida: Araceae) and Sagittaria sp. (Liliopsida: Alismataceae) were placed inside earthen jars filled with 50 L tap water. All earthen jars were treated with Bti formulation at 8g/1000L. Untreated jars with and without aquatic plants were also set up as controls. Fifty laboratory-bred 2nd instar larvae were introduced into each earthen jar. All earthen jars were observed daily. Number of adults emerged was recorded and the larval mortality was calculated. The indicators of effectiveness of Bti for these studies were (i) residual activities of Bti, and (ii) larval mortality in earthen jars with or without aquatic plants. The treated earthen jars containing P. stratiotes and Sagittaria sp. showed significant residual larvicidal effect up to 7 weeks, in comparison to untreated control (p < 0.05). The larval mortality ranged from 77.34-100 for jars with aquatic plants vs 80.66-100 for jars without aquatic plant. Earthen jars treated with Bti without aquatic plants also exhibited significantly longer residual larvicidal activity of up to 10 weeks (p < 0.05). The larval mortality ranged from 12.66-100 for jars with aquatic plants vs 59.34 — 100 for jars without aquatic plant. Thus, earthen jars without aquatic plants exhibited longer residual larvicidal effect compared to those with aquatic plants. This study suggested that containers with aquatic plants for landscaping should be treated more frequently with Bti in view of the shortened residual activity.